Pengelolaan Kesan Simbolik Presiden Jokowi - Sukma, Agus Hitopa (FISIP IBI-K57 Prodi Komunikasi, 2020)
The purpose of research was to find out the management of President Jokowi's leadership communication in terms of managing the symbolic impression displayed in the one-year period of his governance with Vice President Ma'ruf Amin. The research approach uses cultural studies, with the method of studying the literature of media content, especially political opinions. The results showed that during one government, judging by the management of symbolic impressions, President Jokowi more presents himself as an organizer and entrepreneur, so that it does not stand out too prominently the formal aspects of protocol presidency in his daily acts. The leadership challenge is urban geopolitics, namely the co-optation of the city area into a source of legitimacy opposition. This challenge developed into a latent issue of binary opposition that attacked the identity of the President. The post-truth era news phenomenon contributes to the threat of government legitimacy in cyberspace. In the field of education, the element of character building is still weak in the realm of implementation, so the course of government for one year is shown many breakthroughs, but often colored controversially.